2020
DOI: 10.3390/ijms21176312
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPases of the Ras and Rho Families Switch on/off Signaling Pathways in Neurodegenerative Diseases

Abstract: Small guanosine triphosphatases (GTPases) of the Ras superfamily are key regulators of many key cellular events such as proliferation, differentiation, cell cycle regulation, migration, or apoptosis. To control these biological responses, GTPases activity is regulated by guanine nucleotide exchange factors (GEFs), GTPase activating proteins (GAPs), and in some small GTPases also guanine nucleotide dissociation inhibitors (GDIs). Moreover, small GTPases transduce signals by their downstream effector molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 126 publications
(215 reference statements)
1
38
0
Order By: Relevance
“…Rho GTPases are a subfamily of the Ras superfamily proteins and include the key classical proteins RhoA, Rac1, and Cdc42 of the over 20 that have been identified. In addition to critical functions in the nervous system, Rho GTPases regulate cellular behavior such as morphogenesis, survival, proliferation, membrane trafficking, adhesion, and transcriptional activation (Zegers and Friedl, 2014 ; Arrazola Sastre et al, 2020 ; Clayton and Ridley, 2020 ). Rho GTPases are found in all eukaryotic species and are highly conserved which underscores their importance for survival (Hall, 2012 ; Beljan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rho GTPases are a subfamily of the Ras superfamily proteins and include the key classical proteins RhoA, Rac1, and Cdc42 of the over 20 that have been identified. In addition to critical functions in the nervous system, Rho GTPases regulate cellular behavior such as morphogenesis, survival, proliferation, membrane trafficking, adhesion, and transcriptional activation (Zegers and Friedl, 2014 ; Arrazola Sastre et al, 2020 ; Clayton and Ridley, 2020 ). Rho GTPases are found in all eukaryotic species and are highly conserved which underscores their importance for survival (Hall, 2012 ; Beljan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that Ras superfamily GTPases control toxic peptides, such as Aβ42 in amyloid plaques and phosphorylated tau of neurofibrillary tangles, via the MAPK pathway (Gärtner et al, 1999 ). They also induce dendritic spine and synapse loss, which are major AD hallmarks, and Ras controls the L-DOPA-induced dyskinesia in PD as well (Arrazola Sastre et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GTPase activating proteins (GAPs), on the contrary, are responsible for the inactivation of the GTPase by inducing the intrinsic GTPase activity that results in the hydrolysis of the GTP. Finally, guanine nucleotide dissociation inhibitors (GDIs) prevent the dissociation of the GDP from the GTPase, therefore maintaining the GTPase in an inactive state [ 4 , 5 ]. Moreover, small GTPases can also be regulated by post-translational modifications that permit their binding to either specific proteins or membranes.…”
Section: Introductionmentioning
confidence: 99%